Tracking Scientific Output in Robotic Soccer and AI: A Bibliometric Overview - Pashaie, Sajjad; Jung, Timothy; Golmohammadi, Hamed (AI and Tech in Behavioral and Social Sciences, 2025)
This study provides a bibliometric analysis of research related to the topic of robotic soccer and artificial intelligence (AI), mapping the intellectual and thematic landscape of a rapidly evolving interdisciplinary field. Drawing on 79 peer-reviewed articles from the Web of Science database spanning 1997 to 2024, we examine publication trends, citation impact, prolific contributors, institutional output, and core research themes. Utilizing the bibliometrix R package and biblioshiny interface, our analysis reveals that research on robotic soccer has experienced episodic growth, with notable surges linked to global competitions such as RoboCup. Results indicate that topics such as multi-agent collaboration, learning algorithms, autonomous decision-making, and human-robot interaction dominate the field’s motor themes. Influential institutions include Islamic Azad University and Sapienza University of Rome, while key authors such as Peter Stone and Hiroaki Kitano shape the domain’s scholarly foundation. Despite the dominance of technical publications, there remains a research gap in addressing sociotechnical dimensions and integrative AI strategies. This study not only clarifies the structure of the field but also identifies emerging trajectories, offering a strategic foundation for future research on intelligent autonomous systems in sports contexts.